Improvement of Shelf Life and Sensory Quality of Pears Using a Specialized Edible Coating - Virgilio Cruz; Romeo Rojas; Saúl Saucedo-Pompa; Dolores G. Martínez; Antonio F. Aguilera-Carbó; Olga B. Alvarez; Raúl Rodríguez; Judith Ruiz; Cristóbal N. Aguilar (Journal of Chemistry)
An edible coating functionalized with pomegranate polyphenols was designed. Different blends of candelilla wax, gum arabic, jojoba oil, and pomegranate polyphenols were formulated in order to improve the shelf life quality of pears (variety Bartlett), and all formulations were applied by immersion onto the fruit surface. Coated pears with and without polyphenols and uncoated pears (control) were stored under the same conditions. Fruits were analyzed to evaluate changes in their physicochemical, microbiological, and sensorial properties during 30 days of storage at room temperature. Coated pears coded as T13 (candelilla wax 3%, gum arabic 4%, jojoba oil 0.15%, and pomegranate polyphenols 0.015%) extended and improved their shelf life quality due to the minimization of the physic-chemical changes and sensorial properties. Therefore, the results indicated that the formulated edible coating has potential to extend the shelf life and maintain quality of pears. It was probed that coated pears were accepted for consumers as a good product. Edible coating application represents a good alternative to keep pears freshness for longer periods.